Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

Sorry for being a pain :D Use the substitution method to solve the following system of equations. 4x − y = 3 7x − 9y = −2 (1, 1) (6, −3) (6, 1) (1, −3)

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer

SIGN UP FOR FREE
Add y to both sides, then subtract 3 from both sides to isolate y in the first equation. Doing so gives: y = 4x - 3 The expression for y can be substituted into the second equation: 7x - 9y = -2 and after substitution we have 7x - 9(4x - 3) = -2 Now we simplify and solve for x: 7x - 36x + 27 = -2 (7 - 36)x + 27 = -2 -(36 - 7)x + 27 + 2 = 0 -(29)x + 29 = 0 29 = 29x 29/29 = x 1 = x Now plug the value for x back into the one of the original equations to get y.
I don't know how to get the Y... that's why im asking for help..
Do I do it the same way you got x?

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

We isolated y earlier to get y = 4x - 3 If we substitute x = 1 into that equation, we get y.
Oh.. so its D
(1, -3)
y = 4(1) - 3 y = 4 - 3 y = 1 Therefore, the point is (1,1)
Im confused
Re-read it all over again, but slowly.

Not the answer you are looking for?

Search for more explanations.

Ask your own question